Multidrug Resistance and Virulence Factors of Escherichia coli Harboring Plasmid-Mediated Colistin Resistance: mcr-1 and mcr-3 Genes in Contracted Pig Farms in Thailand - Khine, Nwai Oo; Lugsomya, Kittitat; Kaewgun, Benjarong; Honhanrob, Lertrob; Pairojrit, Panupong; Jermprasert, Suthipat; Prapasarakul, Nuvee (Frontiers in Veterinary Science, 2020)
The presence of the plasmid-mediated colistin-resistance encoding mcr gene family in the Enterobacteriaceae is one of the crucial global concerns. The use of colistin in livestock rearing is believed to be the cause of mcr gene spreading and is of impact on public health. The objectives of this research were to detect the frequency and virulent genes of mcr-positive Escherichia coli (MCRPE) in faecal samples from healthy pigs in a contract farming system across Thailand. A total of 696 pooled samples were derived from 80 farms, located in 49 provinces across six regions of Thailand. The colistin-resistant E. coli were screened for and identified by broth microdilution and MALDI-TOF mass spectrometry. The antibiogram was determined using an automated susceptibility machine and the genetic characteristics were investigated for phylogenetic group, replicon type, and virulent genes. In total, 31 of 696 samples were positive, with E. coli containing mcr-1 or mcr-1 and mcr-3 at a prevalence of 4.45% and 0.43%. Phylogenetic groups A and B1 and the IncF and IncFIB replicon types were predominantly found in the MCRPE located in the central area, which presented multidrug-resistant traits against 3–14 types of antimicrobials. Additionally, 19 of 31 isolates were identified as enterotoxigenic E. coli, of which most contained the stap and stb genes. In conclusion, a low carriage rate of mcr-positive E. coli was detected in the largescale farming of healthy pigs. The association between of multidrug-resistance MCRPE and their pathogenic potential should be of concern.